2018
DOI: 10.1002/1873-3468.13298
|View full text |Cite
|
Sign up to set email alerts
|

GLUT6 is a lysosomal transporter that is regulated by inflammatory stimuli and modulates glycolysis in macrophages

Abstract: The solute carrier family is an important protein class governing compound transport across membranes. However, some of its members remain functionally unidentified. We analyzed ChIP‐seq data for the NF‐κB family transcription factor RelA and identified GLUT6 as a functionally uncharacterized transporter that putatively works in inflammatory responses. Inflammatory stimuli increase GLUT6 expression level, although GLUT6‐knockout mice exhibit a subtle phenotype to lipopolysaccharide administration. Metabolomics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 39 publications
(52 reference statements)
1
44
0
Order By: Relevance
“…Of note, CG4607 and CG1208 belong to the SLC2 family of hexose sugar transporters and are orthologous to SLC2A6/GLUT6 or SLC2A8/GLUT8 in humans. Importantly, it has recently been demonstrated that GLUT6 acts as a lysosomal transporter, which is regulated by inflammatory stimuli (Maedera et al, 2019) and is strongly upregulated in macrophages activated by LPS (Caruana et al, 2019). Similarly, in Drosophila, immune activation is energy demanding and glucose may be used as a major source of energy for the production of mature LMs (Bajgar et al, 2015).…”
Section: Lamellocyte Sub-clustering Identifies Lm Intermediates and Smentioning
confidence: 99%
“…Of note, CG4607 and CG1208 belong to the SLC2 family of hexose sugar transporters and are orthologous to SLC2A6/GLUT6 or SLC2A8/GLUT8 in humans. Importantly, it has recently been demonstrated that GLUT6 acts as a lysosomal transporter, which is regulated by inflammatory stimuli (Maedera et al, 2019) and is strongly upregulated in macrophages activated by LPS (Caruana et al, 2019). Similarly, in Drosophila, immune activation is energy demanding and glucose may be used as a major source of energy for the production of mature LMs (Bajgar et al, 2015).…”
Section: Lamellocyte Sub-clustering Identifies Lm Intermediates and Smentioning
confidence: 99%
“…In mice, Glut6 is upregulated by activation of T lymphocytes [51], while in humans, the GLUT6 protein concentration was shown to increase in CD4+ T cells on HIV-1 infection [52]. Recently, GLUT6 was shown to be a lysosomal transporter regulated by inflammatory stimuli and modulating glycolysis in macrophages [53] Glut6 knock-out mice had decreased resistance to LPS-induced shock [53].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly CD8 + EMRAs displayed increased expression of the glucose transporters glut8 and -10. It is tempting to speculate in the light of a recent publication showing that glut6 functions as a glycolysis modulator in inflammatory macrophages without influencing glucose uptake 49 , that glut8 and -10 may act in a similar manner in senescent CD8 + T cells. Glut6, -8 and -10 are all members of the Glut III family of transporters, with glut6 and -8 being very closely located on chromosome 9 and glut10 having a very high affinity for both 2-deoxy-D-glucose and D-galactose 50 , both slow the rate of glycolysis.…”
Section: Discussionmentioning
confidence: 99%